Adaptasi Alat Ukur Regulasi Diri Dalam Belajar Daring - Tejarukmi Mutiara; Tjut Rifameutia (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2021)
Self-regulated learning is crucial learning skill for every learners. Moreover, students are learning online in the midst of the Covid 19 pandemic. This study aims to adapt the scale of Online Self-regulated Learning Questionnaire (OSLQ) developed by Barnard and colleagues (2009) into Bahasa Indonesia and to perform reliability and validity tests. Participants in this study were 399 college students who are doing online learning and are scattered from various regions in Indonesia. The research results show that the scale adaptation which consists of 24 items are reliable with a Cronbach’s Alpha coefficient .915 and valid with the construct validity of the Corrected Item Total Correlation coefficient are on range .409 - .708. The construct validity based on Confirmatory Factor Analysis also shows the model fit. Therefore, the adapted scale can be used within Indonesian participants.